DISSOLUTION OF IRON HYDROXIDES BY MARINE BACTERIAL SIDEROPHORE - Yoshida T.; Hayashi K.I.; Ohmoto H. (My University, 2002)
A series of laboratory experiments was conducted to investigate the dissolution behavior of goethite and poorly crystalline iron hydroxide (PCIH) in the presence of siderophore produced by a marine bacterium, Alteromonas haloplanktis. The amounts of siderophore in the experimental solutions are expressed by the iron complexing capacity (ICC). The experimental data indicate that both the dissolution rates and solubilities of ferric hydroxides increase with increasing contents of siderophore and [H+]. For example, in a solution of pH=8 and ICC=12 μM, the iron content of solution increased from <0.1 to 1.3 μM by reaction with PCIH for 80 h. This Fe content is more than 50 times the solubility value of amorphous Fe(OH)3 in pure water at pH=8. At pH=4, with increasing ICC value from 0 to 12.9 μM, the dissolution rate of goethite increased from 1.5 to 9.5 (nM/h/m2) and that of PCIH increased from 0.4 to 3.4 (nM/h/m2). At ICC=12.9 μM, with increasing pH from 4 to 6.8, the dissolution rate of goethite decreased from 9.5 to 1.9 nM/h/m2, whereas that of PCIH decreased from 3.4 to 0.7 nM/h/m2. Our study suggests that most of the iron utilized by phytoplankton in the oceans may be liberated from ferric hydroxides in aeolian particles by siderophores generated by marine bacteria.
Keywords: DISSOLUTION; SIDEROPHORE; IRON HYDROXIDE; MARINE BACTERIUM